Pengaruh Pendekatan Pembelajaran Berdiferensiasi Terhadap Kemampuan Berpikir Kreatif Bahasa Indonesia Siswa Kelas IV SD Negeri 141 Lilina Ajangale Kabupaten Bone - Alfian, Muhammad Alfian Solo; Hafid, Abd; Asriadi, Asriadi (MACCA : Science-Edu Journal, 2025)
This research is a quantitative pre-experimental study that aims to determine the effect of the differentiated learning approach on the creative thinking ability in the Indonesian language of fourth-grade students at SD Negeri 141 Lilina Ajangale, Bone Regency. This research employs a One Group Pre-test-Post-test design. The variables in this research consist of the differentiated learning approach as the independent variable and students' creative thinking ability as the dependent variable. The population of this research includes all fourth-grade students at SD Negeri 141 Lilina Ajangale, totaling 20 students, with a saturated sampling technique used for sample selection. Research data were obtained through a creative thinking ability test conducted before (pre-test) and after (post-test) the implementation of the differentiated learning approach. Data analysis techniques involved descriptive and inferential analysis using the Paired Sample t-Test. The results indicate that before the implementation of the differentiated learning approach, the students' average test score was 42.75, classified as low. After the implementation, the average test score increased to 71.25. Statistical analysis results show a significant difference in students' creative thinking ability before and after using the differentiated learning approach. Therefore, it can be concluded that the differentiated learning approach has a significant effect on improving the creative thinking ability in the Indonesian language of fourth-grade students at SD Negeri 141 Lilina Ajangale, Bone Regency.